The world's biomes desert to rainforest - AIMS Multimedia (Chatsworth, CA : AIMS Multimedia, 1997)
Introduces how various physical factors determine the climate of a biome, and in turn, the density of life within a given biome. Takes the viewer on a journey through rainforests, deserts, grasslands, coniferous forests, alpine tundra, deciduous forests, and marine and freshwater biomes
Title from diisc label
Installation guide : Macintosh, drag folder to hard drive, the double click on the program icon ; Windows, run'INSTALLE.EXE' from the cd-rom, then double click the program icon
Keywords: Biotic communities -- Juvenile literature; Ecology -- Juvenile literature; Forest ecology -- Juvenile literature; Grassland ecology -- Juvenile literature; Desert ecology -- Juvenile literature